METHODOLOGY OF FORMATION OF COMMUNICATIVE COMPETENCE OF VOCATIONAL SCHOOL STUDENTS BY IMPROVING THEIR PREPARATION FOR PROFESSIONAL ACTIVITY - Agalieva Xabiba Narmaxmad qizi (Journals Park Publishing, 2024)
The development of communicative competence is crucial for vocational school students as it enhances their ability to effectively interact in a professional environment. This article presents a comprehensive methodology aimed at improving students' communicative competence through enhanced preparation for their future professional activities. The methodology incorporates various pedagogical approaches, strategies, and techniques to ensure the successful integration of communication skills within vocational education.
Keywords: Communicative competence, Vocational school students, Professional activity, Methodology, Curriculum development, Authentic learning, Communication workshops, Technology integration, Assessment and feedback, Pedagogical strategies, CLT (Communicative Language Teaching).